2015
DOI: 10.1016/j.dental.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight and galloylation affect grape seed extract constituents’ ability to cross-link dentin collagen in clinically relevant time

Abstract: Objective To investigate the relationship between the structures of polyphenolic compounds found in grape seed extract (GSE) and their activity in cross-linking dentin collagen in clinically relevant settings. Methods Representative monomeric and dimeric GSE constituents including (+)-catechin (pCT), (−)-catechin (CT), (−)-epicatechin (EC), (−)-epigallocatechin (EGC), (−)-epicatechin gallate (ECG), (−)-epigallocatechin gallate (EGCG), procyanidin B2 and a pCT-pCT dimer were purchased or synthesized. GSE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 36 publications
0
38
0
2
Order By: Relevance
“…Epicatechin and its derivatives are known to have great potential for anti-inflammatory 7 and anti-cancer effects 4 , 8 . Furthermore, they are also used as crosslinking agents 3 , 15 . However, there have been no studies regarding the effect of ECN on human dental pulp cells (hDPCs) or on the cells cultured in a collagen hydrogel scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Epicatechin and its derivatives are known to have great potential for anti-inflammatory 7 and anti-cancer effects 4 , 8 . Furthermore, they are also used as crosslinking agents 3 , 15 . However, there have been no studies regarding the effect of ECN on human dental pulp cells (hDPCs) or on the cells cultured in a collagen hydrogel scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PAs from different sources exerted distinct protective effects on dentin. [28][29][30] The proportion of PA oligomers is often regarded as a key indicator of their effects, based on their abilities to scavenge radicals and resist oxidation. However, oligomers with a low degree of polymerization exhibit insufficient convergence capacity and weak binding to dentin collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the role of proanthocyanidin molecules in GSE solution with glycerin could not be optimum to increase the microhardness of dentin in the root canal. In a previous study by Liu et al (2015), the small molecular size of proanthocyanidin reported providing the best results in triggering an increase in dentin collagen's mechanical properties [30].…”
Section: The Role Of Proanthocyanidin In Gsementioning
confidence: 98%